Unsustainability of Obesity: Metabolic Food Waste - Serafini, Mauro; Toti, Elisabetta (Frontiers in Nutrition, 2016)
The obesity burden, with 1.5 billion overweight and 500 million obese worldwide, significantly increased the risk for degenerative diseases. Excessive consumption of foods that are energy dense lead to obesity, which represents a titanic cost for not only the world’s health systems but also a substantial ecological cost to the environment. The waste of resources and the unnecessary GHGs emission, due to “obesigen” consumption of foods, have been ignored so far in practical assessments of ecological impacts. Our position is that food eaten above physiological needs, manifesting as obesity, should be considered waste. In this study, we developed a new indicator, Metabolic Food Waste (MFW(kg of food)), corresponding to the amount of food leading to Excess Body Fat (EBF) and its impact on environment expressed as carbon (MFW(kgCO2eq)), water (MFW(x 10 L)) and land footprint (MFW(x10 m2)). Results shows that the average amount of MFW(kg of food) was of 63.1 and 127.2 kg per capita in a observational study on sixty overweight and obese subjects. Animal products contributed mostly to MFW(kg of food) in both OW (24.3 kg) and OB (46.5 kg), followed by cereals, legumes and starchy roots (19.4 kg OW; 38.9 kg OB), sugar and sweets (9.0 kg OW; 16.4 kg OB) and alcoholic beverages (7.5 kg OW; 20.1 kg OB). When dietary intake corresponding to MFW was transformed in ecological indexes, animal products displayed the highest values for carbon emissions, water consumption and land use in both OW and OB followed by cereals, legumes and starchy roots. The estimated MFW(kg of food) of the Italian population resulted to be 2.081 million kg of food for OB and OW. Reducing obesity will make a contribution toward achieving sustainable and functional diets, preserving and re-allocating natural resources for fighting hunger and malnutrition and reducing GHGs emissions. Although further evidences in epidemiological studies are needed, MFW represents an innovative and reliable tool to unravel the diet-environment-health trilemma.